Asian-Pacific law & policy journal APL & PJ (William S. Richardson School of Law, University of Hawaii, 1999)
Provides a forum for the presentation and discussion of legal, policy-based, and socio-economic issues that affect East Asia and Polynesia, the individual nations of those regions, and Australia.